2017
DOI: 10.17305/bjbms.2017.2530
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the neutrophil-to-lymphocyte ratio (NLR) in patients with operable ampullary carcinoma

Abstract: Ampullary carcinoma or cancer of the ampulla of Vater is a rare malignancy with a high recurrence rate. Although cost-effective biomarkers, such as neutrophil-to-lymphocyte ratio (NLR), have been investigated in other cancers for predicting postoperative prognosis in patients, studies on the role of NLR in ampullary cancer are scarce. Here we aimed to evaluate the prognostic significance of preoperative NLR in patients with operable ampullary carcinoma. We retrospectively reviewed 87 patients who underwent pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Lymphocyte counts can reflect endogenous cancer resistance of the immune system 27,28. By the combination of neutrophils and lymphocytes, high NLR level has been shown to be a promising indicator of poor prognosis for patients with cancer 2931. In this study, the optimal cutoff value of 2.93 for the NLR was found to exhibit superior prognostic value for the DFS of TNBC.…”
Section: Discussionmentioning
confidence: 68%
“…Lymphocyte counts can reflect endogenous cancer resistance of the immune system 27,28. By the combination of neutrophils and lymphocytes, high NLR level has been shown to be a promising indicator of poor prognosis for patients with cancer 2931. In this study, the optimal cutoff value of 2.93 for the NLR was found to exhibit superior prognostic value for the DFS of TNBC.…”
Section: Discussionmentioning
confidence: 68%
“…[12] Four studies evaluated NLR in patients with PPC. [10,[12][13][14] Garcea et al demonstrated that NLR has no pre-operative value in discriminating between operable and non-operable disease and has no value in detecting occult disease. [10] Kumamoto et al found that a higher NLR as associated with major complications.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Demirci et al found that an NLR of more than 3 was associated with overall survival and disease-free survival. [14] Three studies aimed to assess the role of PLR in patients with PC. [10,[15][16][17] Garcea et al showed no role of PLR in assessing the benefit of staging laparoscopy in PPC patients.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophil-lymphocyte ratio (NLR) is a significant prognostic marker in many tumor therapies (49)(50)(51)(52)(53); high NLR indicates host inflammation and is associated with shorter OS in several tumor types (49). Comparisons of NLR before and after treatment with PD-1/PD-L1 inhibitors showed that patients with NLR ≥4 were found to have shorter OS and disease progression-free time before treatment (54).…”
Section: Neutrophil/lymphocyte Ratiomentioning
confidence: 99%